The roles of microstructural anisotropy in tribo-corrosion performance of one certain laser cladding Fe-based alloy - Weitao Sun; Xuehong Huang; Jian Zhang; Bin Wang; Xiaoliang Liu (Friction)
Abstract Because of the microstructural anisotropy for laser cladding materials, the tribo-corrosion performance can vary significantly with different directions. In this study, one certain Fe-based coating was fabricated by laser cladding. To study the effects of anisotropy, three working surfaces (0°, 45°, and 90° to the building direction) were machined from the laser cladding samples; as-cast samples with an approximately homogeneous structure were prepared as controls. The tribo-corrosion tests were conducted in a 3.5 wt% NaCl solution with varying normal loads (5, 10, and 15 N). The results demonstrated that the 45° surface has superior friction stability, corrosion resistance, and wear resistance. This was directly related to the crystal orientation and grain boundary density. In addition, a refined microstructure may enhance tribo-corrosion properties by increasing deformation resistance and decreasing surface activity.